Morning or evening exercise : effects on the heart rate circadian rhythm above the Arctic Circle - G. Calogiuri; A. Weydahl; S. Beldo; A. Montaruli (European College of Sport Science, 2010)
The potency of exercise as a nonphotic time cue compared to the solar cycle in influencing entrainment (organism synchronization within the 24-h period) has yet to be defined. Above the Arctic Circle during winter the sun remains below the horizon for several weeks and during summer remains above the horizon for several weeks. The goal of the present study was to investigate the effects related to exercising time on the circadian structure under conditions of lack of daylight and continuous daylight. The experiments were carried out at 70° North, above the Arctic Circle. Ten healthy females (age 24±5 years) were divided into two groups: an exercise and a control group. The subjects in the exercise group performed the same exercise routine at two different times of day (0900 and 1800 hours) both in January (twilight period) and in May (continuous daylight period). Continuous heart rate data were collected and analysed by the cosinor method. The acrophase values were significantly modified in the exercise group during evening exercise in January showing a delay compared with morning exercise and compared with the control group (3 h and 1. 5 h, respectively), while in May this effect was not seen. The results indicate that in continuous daylight, the potency of exercise in modulating the circadian phase seems to be suppressed. However, these findings need to be verified in a larger poulation.